Aplikasi Penggajian Karyawan Tetap dengan Menggunakan Appsheet pada PT PLN Unit Induk Pembangunan Jawa Bagian Tengah - Suprihatin, Eti; Wulandari, Reni (STIE Atma Bhakti, 2025)
This research aims to develop an AppSheet-based application that can assist PT. PLN UIP JBT in optimizing the use of its payroll application. This facility provides incentives by simplifying payroll data management, enabling more in-depth analysis of various payroll components, and ensuring timely and accurate salary distribution to employees. With the implementation of this application, it is expected that payroll management at PT. PLN UIP JBT will become more efficient and effective, and employee satisfaction will be enhanced through payroll transparency and accuracy.